Rancang Bangun Untuk Sistem Penyiraman Pada Tanaman Herbal Jahe Merah Berbasis Node MCU ESP32 - Surya Prasetya, Ari; Islamiyah, mufidatul (JURNAL SISTEM KOMPUTER ASIA, 2024)
Soil Moisture is a major factor affecting ginger growth. For ginger to grow well, adequate water supply and a suitable environment are required. Currently, manual irrigation is inefficient because it requires a lot of energy and constant monitoring to ensure the plants receive enough water. This makes it difficult for plant owners who want to leave their plants for an extended period due to concerns about the plants lacking water and nutrients.To address this issue, an automatic irrigation system for ginger has been developed. This system is designed to reduce dependence on manual irrigation, which requires direct supervision. The automatic irrigation system uses advanced technology, such as the Nodemcu ESP32 as the control center and YL 69 soil moisture sensors. This tool not only facilitates ginger maintenance but also improves resource efficiency and reduces the need for human supervision. In this study, an automatic irrigation tool was developed with the goal of reducing overwatering and underwatering of ginger plants. The tool has been tested and analyzed, yielding satisfactory results to achieve the expected goals of reducing the risk of overwatering and underwatering in red ginger plants.